Persepsi UPZ dan Non UPZ Tingkat Masjid Terhadap BAZNAS Kota Tangerang Selatan - Faishal Robbani; Mohammad Nur Rianto Al Arif (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
This study aims to determine the perception of UPZ and Non-UPZ Mosque Level towards BAZNAS South Tangerang City. The object of this research is mosques in South Tangerang City. The factors studied are transparency, accountability and the socialization of the BAZNAS program. The research method used is a quantitative approach with logistic regression analysis techniques. The sample of this study is the mosques of South Tangerang City with the criteria of a mosque that has a large potential of zakat totaling 30 mosques obtained from the calculation using the Slovin formula. The instrument used in this study was a questionnaire. The results of this study indicate that the perception of UPZ and Non-UPZ Mosque Level towards BAZNAS South Tangerang City is influenced by several problems. These problems can be categorized, namely lack of public trust due to lack of transparency and accountability of the government or agency that deals with zakat funds, then the lack of public understanding of UPZ due to the lack of socialization to educate the public.